Platelets and Fibrinolysis - Joist, J. Heinrich (Thrombosis and Haemostasis, 1977)
Blood platelets play a crucial role in the response of blood to vascular injury through adherence to exposed subendothelial vessel wall structures, the subsequent release of substances which trigger platelet aggregation, and release-associated changes in platelet surface properties which facilitate the interaction of coagulation factors, leading to the formation of fibrin necessary for stabilization of the initial hemostatic plug. There is substantial evidence from in vitro studies to suggest that platelets may also affect the fibrinolytic plasminogen-plasmin system thought to be one of the important hemostatic regulatory mechanisms preventing inappropriate extension of the hemostatic plug which may lead to thrombotic vessel occlusion. In this paper, the published experimental evidence concerning the effects of platelets and platelet-associated factors on the activation and function of the plasminogen-plasmin system is reviewed. The experimental findings indicate that platelets may contribute to fibrin clot stabilization through the release of substances from their storage organelles which inhibit both plasminogen activation and the action of plasmin. The physiologic and pathophysiologic significance of platelet-mediated inhibition of fibrinolysis by plasmin, as well as other potentially important plasma and cellular fibrinolytic enzymes, is still largely subject to speculation and appears to be an important area for future investigation.